(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
A portion of a deep-sea core that contains a purely pelagic low- sedimentation-rate succession, extends in time from approximately 260,000 to 160,000 y BP, includes the Gephyrocapsa oceanica/Emiliania huxleyi zonal boundary, and the four sapropels S-9 through S-6, was investigated in detail. Carbonate content, org C content, grain-size analysis, composition of the sand-size sediment fraction, isotopic composition of O and C were measured with an observation point every approximately 300Oy. Cyclicity represented by the sapropels is fairly regular and is of the order of 20,000 y (Milankovitch precession cycles). The grain-size increases consistently in the sapropels, whereas the carbonate content usually decreases, with the exception of S-6. Biogenic components are always dominant, whereas organic matter abounds in sapropels, especially in S-7 which records 9% org C. The number of planktonic foraminifers ranges around a few thousands per gram of sediment; increases of one order of magnitude are noticed in sapropels S-6 and S-8, thus supporting increased productivity, as suggested by the dominance of Neogloboquadrina dutertrei. The consistent decrease in the number of pteropod fragments in all sapropel layers is attributed to dissolution of the easily dissolvable aragonitic tests in the deep-sea acidic environment.